Generation of Food-Grade Recombinant Lactic Acid Bacterium Strains by Site-Specific Recombination - Martín, M. Cruz (American Society for Microbiology, 2000)
The construction of a delivery and clearing system for the generation of food-grade recombinant lactic acid bacterium strains, based on the use of an integrase (Int) and a resolvo-invertase (β-recombinase) and their respective target sites (attP-attB and six, respectively) is reported. The delivery system contains a heterologous replication origin and antibiotic resistance markers surrounded by two directly oriented six sites, a multiple cloning site where passenger DNA could be inserted (e.g., the cI gene of bacteriophage A2), the int gene, and the attP site of phage A2. The clearing system provides a plasmid-borne gene encoding β-recombinase. The nonreplicative vector-borne delivery system was transformed into Lactobacillus casei ATCC 393 and, by site-specific recombination, integrated as a single copy in an orientation- and Int-dependent manner into the attB site present in the genome of the host strain. The transfer of the clearing system into this strain, with the subsequent expression of the β-recombinase, led to site-specific DNA resolution of the non-food-grade DNA. These methods were validated by the construction of a stable food-grade L. casei ATCC 393-derived strain completely immune to phage A2 infection during milk fermentation.